Aplikasi Try Out Untuk Sekolah Menengah Atas Berbasis Android - ., Paryanta; - STMIK AUB Surakarta, Putri Septiana Ismayati (IJNS - Indonesian Journal on Networking and Security, 2020)
ABSTRACT - The implementation of Try Out is currently still being carried out in schools, so there is a limited time for students to carry out these activities and there are often students who cannot participate in the simulation due to various reasons, such as illness. The results of the implementation of the preparation for the implementation of the UNBK were not satisfactory, this is because the practice questions or try outs must be carried out in schools so that students have limited time to practice questions and have to wait for the schedule. The purpose of this study was to build an Android-based Try Out Application in Senior High Schools to help students provide flexibility and time freedom to practice national exam questions. In building these applications the method used in system development uses the waterfall method, while the system design uses an object-oriented model with UML (Unified Modeling Language), consisting of Use Case Diagrams, Class Diagrams, Activity Diagrams and Squence Diagrams, while the system design uses programming languages. Java, HTML, PHP, My SQL as database processing. Andorid Studio version 3.01 as a framework. The results of this research are in the form of a Try Out Application software which contains practice questions (question bank) of the national exam along with the answer keys and discussion of each of these questions, and can be done at any time without any time limit. Keywords: Application, Implementation, Try Out, Problem ABSTRACT - Pelaksanaan Try Out saat ini masih dilaksanakan di sekolah, sehingga terjadi keterbatasan waktu siswa dalam melaksanakan kegiatan tersebut dan sering kali ada siswa yang tidak dapat mengikuti simulasi tersebut dikarenakan berbagai alasan misalnya sakit. Penerapan persiapan pelaksanaan UNBK tersebut diatas hasilnya belum memuaskan, ini dikarenakan latihan-latihan soal atau try out harus dilaksanakan di sekolah sehingga siswa terbatas waktu dalam berlatih soal-soal dan harus menunggu jadwaL Tujuan penelitian ini adalah membangun Aplikasi Try Out Berbasis Android pada Sekolah Menengah Atas untuk membantu siswa memberikan keleluasaan dan kebebasan waktu untuk berlatih soal-soal ujian nasional. Dalam membangun aplikasi tersebut metode yang digunakan dalam pengembangan sistem menggunakan metode waterfall, sedangkan perancangan sistem menggunakan model berorientasi obyek dengan UML ( Unified Moddeling Languange ), terdiri dari Use Case Diagram, Class Diagram, Activity Diagram dam Squence Diagram, sedangkan pembuatan sistem menggunakan bahasa pemrograman Java, HTML, PHP, My SQL sebagai pengolahan database. Andorid Studio versi 3.01 sebagai framework. Hasil dari penelitian ini adalah berupa software Aplikasi Try Out yang didalamnya berisi soal-soal latihan (bank soal) ujian nasional berikut kunci jawaban serta pembahasan dari setiap soal tersebut, dan dapat dikerjakan setiap saat tanpa ada batasan waktu. Kata kunci : Aplikasi, Pelaksnaan, Try Out, Soal